Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/la801547u
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Alumina on SBA-15: Effect of Surface Roughness

Abstract: Alumina-grafted materials were prepared by postsynthesis alumination of mesoporous SBA-15 silica in an aqueous solution of aluminum chlorhydrol. Prepared samples were characterized by nitrogen adsorption, scanning electron microscopy, X-ray powder diffraction, and (27)Al magic-angle-spinning NMR. The successive grafting of alumina on SBA-15 leads to a gradual filling of the corona surrounding the mesopores. As a consequence smoothing of the mesopore surface takes place. The in-depth analysis of nitrogen adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 29 publications
(48 reference statements)
4
61
0
1
Order By: Relevance
“…The Pd II -diamine complexes in more accessible locations will in turn have a greater chance to come off or decompose at higher temperatures. On the other hand, the organosilanes grafted in the second step may end up in the microporous or corrugated leftover porous structures that SBA-15 type materials typically have, [48,49] making them decompose rather slowly. The presence of the organoamine and palladium catalytic groups in the bifunctional catalysts was further corroborated by elemental analyses and ICP-AES, respectively (Table 2).…”
Section: [D] This Results Reflects Also the % Yield Of The P-iodo-β-nimentioning
confidence: 99%
“…The Pd II -diamine complexes in more accessible locations will in turn have a greater chance to come off or decompose at higher temperatures. On the other hand, the organosilanes grafted in the second step may end up in the microporous or corrugated leftover porous structures that SBA-15 type materials typically have, [48,49] making them decompose rather slowly. The presence of the organoamine and palladium catalytic groups in the bifunctional catalysts was further corroborated by elemental analyses and ICP-AES, respectively (Table 2).…”
Section: [D] This Results Reflects Also the % Yield Of The P-iodo-β-nimentioning
confidence: 99%
“…It can be seen that normalized pore volume (NPV) decreased linearly with increasing V 2 O 5 loading. This implied that V 2 O 5 species are present inside the pores of the support [18].…”
Section: N 2 Adsorption Measurementmentioning
confidence: 99%
“…4). It was reported that three distinct signals with maximum values centered at 3, 34 and 56 ppm should be assigned to octahedral Al (oct), pentahedral Al (pen) and tetrahedral Al (tet) atoms, respectively (Zukal et al 2008). …”
Section: Support and Catalyst Characterizationmentioning
confidence: 99%
“…Up to now, various pure silica mesoporous materials, such as MCM-41 (Goldbourt et al 2002;Landau et al 2001), SBA-15 (Zukal et al 2008;Baca et al 2008) and KIT-1 (Ryoo and Kim 1997;Jun and Ryoo 2000), have been employed as templates in many investigations concerning alumination of SiO 2 surfaces through grafting technology. Several researchers have investigated the HDS performance of catalysts supported on alumina-grafted materials.…”
Section: Introductionmentioning
confidence: 99%